Ultrafast exciton dynamics and two-photon pumped lasing from ZnSe nanowires - Xing, Guichuan (2013)
The carrier recombination dynamics in ZnSe nanowires (NWs) remain poorly understood despite more than a decade of research since their inception in 2001. Herein, through a comprehensive pump fluence- and temperature-dependent two-photon excitation (TPE) study, a clear picture of the carrier relaxation pathways, intrinsic lifetimes, exciton oscillator strengths, and exciton-phonon interactions is presented for this NW system. Contrary to a common perception that the higher pump intensities needed to achieve two-photon-excited photoluminescence correspond to a higher exciton density threshold (nth) for two-photon pumped lasing, it is found that a much lower nth is needed to achieve lasing with TPE compared to single-photon excitation (SPE) of the same ZnSe NWs. This measurement is further supported by the greatly enhanced lasing action photostability characteristics of the ZnSe NWs under TPE. These findings have significant implications on the design and the tailoring of the optoelectronic properties of nanowire lasers.